ROLE OF PLEURAL BIOPSY IN THE EVALUATION OF THE PLEURAL EFFUSION - BABU, RESHMA S; JADHAV, ULHAS; GHEWADE, BABAJI (International Journal of Psychosocial Rehabilitation, 2020)
In a hospital where thoracoscopy is not available, pleural biopsy can be used for the diagnosis of exudative effusion in conditi0ons where malignancy is doubted and when results of pleural effusion are not conclusive. In a country with limited resources like India pleural biopsy can still be used for the diagnosis of pleural effusion. 1.To study use of pleural biopsy in evaluation of pleural effusion.2. To correlate the pleural biopsy with biochemical and cytological findings of pleural fluid.3. To find the complications of pleural biopsy. An observational cross sectional study will be conducted in Acharya Vinoba Bhave Rural Hospital among 70 patients admitted with exudative pleural effusion. Pleural biopsy will be done and pleural fluid investigations will be send. Cause of pleural effusion can be obtained from the pleural biopsy. Malignancy and tuberculosis are the most frequent reasons of pleural effusion according to previous studies. Whether pleural biopsy gives definitive diagnosis as compared to pleural fluid cytology or pleural fluid CBNAAT. Pleural biopsy is associated with minimal post procedure complications Pleural Biopsy helps in the identifying the etiology of undiagnosed pleural effusion. Complications associated with pleural biopsy is less. Closed pleural biopsy helps identifying cause of the exudative pleural effusion when thoracoscopy is not available.